Familismo: How Eight Categories of Needs Are Met in Hispanic American Families Within the Context of Familism - Rama, Catherine R.; Harris, Victor W.; Speegle, Kyra; Nelson, Nelly; Moen, Dan; Harris, Heidi Jones (Advances in Social Sciences Research Journal, 2020)
The purpose of this qualitative study was to assess how eight categories of needs are met in Hispanic American families within the context of familism. Derived from Maslow’s Hierarchy of Needs, the categories examined include the need to: (1) feel safe; (2) belong; (3) develop a positive self-concept; (4) experience close real-love relationships; (5) receive respect; (6) feel worthwhile; (7) feel competent; and, (8) experience growth. Study participants completed an online open-ended questionnaire that focused on how needs were met in families within the Hispanic culture. A conceptual model of how these needs can be met in Hispanic American families within a context of familism is proposed. Implications for how educators and practitioners can help Hispanic Americans meet these eight categories of needs and thus strengthen families are discussed.